Quantitative ultrasound and biochemical parameters for the assessment of osteopenia in preterm infants - BEREKET, ABDULLAH; BİLGEN, HÜLYA SELVA (TAYLOR & FRANCIS LTD, 2007)
Objective. Our study aimed to evaluate the feasibility of quantitative ultrasound (QUS) evaluation in osteopenia of prematurity and to compare the results to biochemical parameters. Methods. QUS assessment of bone was performed at the end of the first postnatal week and at term-corrected age (CA) in premature infants (N = 30) and within the first week in full-term infants (N = 25). On the same day of measurement of QUS, the serum calcium, phosphorus (inorganic), and alkaline phosphatase (ALP) activity were measured in the preterm infants. Results. The median of tibia z score at term-CA in premature infants was significantly lower compared to that of first postnatal week (-1 and 0.4, respectively; p < 0.0001) and it was also lower than that of term-matched controls (0.0; p = 0.001). Preterm infants at term-CA had lower weights and lengths in comparison to term infants. The median ALP value was 585 IU/L at the first postnatal week and 703 IU/L at term-CA in preterm infants (p = 0.003). The median tibia z score of infants with ALP >= 900 IU/L was significantly lower than that of the infants with ALP < 900 IU/L (-1.4 vs. 0.1; p = 0.001). An inverse correlation was found between ALP levels and tibia z score at term-CA in preterm infants (rho = -0.61, p = 0.01). Conclusions. Bone density of preterm infants at term-CA was lower than that at first postnatal week. Serum ALP levels increased during the first postnatal weeks. The tibia z scores were correlated to serum ALP levels. QUS is a good screening tool for the detection of osteopenia.
Keywords: quantitative ultrasound; osteopenia of prematurity; HIGH-TURNOVER OSTEOPENIA; BONE-MINERAL CONTENT; BODY-COMPOSITION; ALKALINE-PHOSPHATASE; WEIGHT; GROWTH; TERM